One-year surveillance of Chlamydia spp. infection in stray cats from northeastern Italy - Bellinati, Laura; Ceglie, Letizia; Mazzotta, Elisa; Campalto, Mery; Lucchese, Laura; Natale, Alda (Frontiers in Veterinary Science, 2025)
Stray cats potentially act as reservoir for zoonotic agents, posing a risk of exposure to humans and domestic cats. The most prevalent Chlamydiaceae species in cats is Chlamydia (C.) felis, which is frequently associated with conjunctivitis and/or upper respiratory disease. The zoonotic potential of C. felis is believed to be relatively low, although exposure is possible through handling infected cats, by contact with their aerosol, and via fomites. Infection is more frequent in conditions of overcrowding, stress, poor hygiene and impairment of the immune system. For this reason, stray cats appear to be particularly susceptible to this pathogen. Aim of the study was to identify the molecular occurrence of Chlamydiaceae in stray and colony cats. Between May 2021 and June 2022, in seven provinces of northeastern Italy, veterinary services officers collected oropharyngeal swabs from 379 stray and colony cats. The samples were screened for Chlamydiaceae by real-time PCR targeting a 23S gene fragment. Positive samples were further analyzed either by a C. felis-specific qPCR or by amplification and sequencing of a 16S rRNA gene fragment. Overall, 7.7% of the cats tested positive for Chlamydia spp., and all were identified as C. felis. Among the positive individuals, only one exhibited respiratory symptoms. The analysis of anamnestic data revealed a significantly higher frequency of C. felis in male intact cats during the spring season, suggesting a potential behavioral aspect of this infection. Although the zoonotic risk of this Chlamydia species is low, it would be prudent to exercise caution when handling stray cats.